The importance of surgical access in the treatment of patients with prostate cancer and abnormal prostate anatomy - A. V. Zyryanov; A. S. Surikov; A. A. Keln; A. V. Ponomarev; V. G. Sobenin (Сибирский онкологический журнал, 2022)
Background. The increased volume of the prostate in patients with confirmed prostate cancer (pc) is observed in 10 % of cases. The limitations of external beam radiotherapy and brachytherapy associated with large prostate volume and obstructive symptoms define radical prostatectomy (Rp) as the only possible treatment for prostate cancer in these patients. The purpose of the study was to determine the importance of the surgical approach in radical prostatectomy in patients with abnormal anatomy of the prostate. Material and methods. The study group consisted of patients with a prostate volume of more than 80 cm3 (n=40) who underwent a robot prostatectomy. The comparison group was represented by patients also selected by the prostate volume ≥ 80 cm3, who underwent classical open prostatectomy (n=44). The groups were comparable in age and psa level. The average prostate volume in the study group was 112.2 ± 26 cm 3(80–195 cm 3). The average prostate volume in the comparison group was 109.8 ± 18.7 cm3 (80–158 cm 3) (р>0.05). Both groups had favorable morphological characteristics. Results. The average surgery time difference was 65 minutes in favor of the open prostatectomy (p<0.05). The average blood loss volume in the study group was 282.5 ± 227.5 ml (50–1000 ml). The average blood loss volume in the group with open prostatectomy was 505.7 ± 382.3 ml (50–2000 ml). Positive surgical margin in the robotic prostatectomy was not detected, at 6.9 % in the group with open prostatectomy (p<0.05). According to the criterion of urinary continence, the best results were obtained in the group of robotic prostatectomy (p<0.05). Overall and relapse-free 5-year survival did not show a statistically significant difference. Conclusion. The use of robotic prostatectomy in a group of patients with a large prostate volume (≥ 80 cm3) allows us to achieve better functional and oncological outcomes.